If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 86 = 110 Reorder the terms: 86 + x = 110 Solving 86 + x = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-86' to each side of the equation. 86 + -86 + x = 110 + -86 Combine like terms: 86 + -86 = 0 0 + x = 110 + -86 x = 110 + -86 Combine like terms: 110 + -86 = 24 x = 24 Simplifying x = 24
| (x/4)=12 | | 1/2+r=31/4 | | 1/2+r=3/1/4 | | (-x/10)=13 | | 7-2b=10 | | -24x-6/-2=15 | | 4x+9x+3x=30 | | 5+2y=2y+6 | | 5x^2-7/2x=1/2x+1 | | 5x-3=8+4x | | (x/17)=4 | | x^2/3+2x=1+x | | 6y+2(y-4)=4(y+1)-3 | | (x/17)=2 | | -29=-5b+6 | | (-x/10)=3 | | 5(x-1)-8=2x+3(-3+x) | | -20=10+6r | | x^2/5-3x^1/5+2=0 | | X/9-6=-5 | | -4y-9=2y+9 | | 9+n/6=8 | | 6(8-z)/5=-z | | m^2=6m-10 | | 3-2r=-35 | | 5x*2+9x-9=4 | | 5-5x=-70 | | -22=p-3 | | -4(5x-2)+9=-20x+17 | | 8p=-10p+36 | | Y+4/7=-3 | | 6(4x-2)=24x-12 |